Cationic Solid Lipid Nanoparticles Loaded by Cystein Proteinase Genes as a Novel anti-Leishmaniasis DNA Vaccine Delivery System: Characterization and in vitro Evaluations - Delaram Doroud; Alireza Vatanara; Farnaz Zahedifard; Elham Gholami; Rouhollah Vahabpour; Abdolhossein Rouholamini Najafabadi; Sima Rafati (Frontiers Media S.A., 2010)
Purpose: Leishmaniasis is a major health problem in many tropical and sub-tropical countries and development of a safe and easily-available vaccine has high priority. Although several antigens potentially capable of inducing protective immunity have been studied, in the absence of pharmaceutical industry interest they have remained as fine publications only. Amongst them, Cathepsin L-like cysteine proteinases (CPs) have received considerable attention and type I and II CPs have been used in a heterologous prime-boost vaccination regime for experimental visceral leishmaniasis in dogs. Due to the promising results of the mentioned vaccination regime, we aimed to evaluate cationic solid lipid nanoparticles (cSLNs) for in vitro delivery of cpa, cpb and cpbCTE intended to be used as a cocktail DNA vaccine in our forthcoming studies. Methods: cSLNs were formulated of cetyl palmitate, cholesterol, DOTAP and Tween 80 via melt emulsification method followed by high shear homogenization. Different formulations were prepared by anchoring pDNAs on the surface of cSLNs via charge interaction. The formulations were characterized according to their size and zeta potential as well as pDNA integrity and stability against DNase I treatment. Lipoplexes' cytotoxicity was investigated on COS-7 cells by MTT test. The effect of the DOTAP:pDNA ratio on protection ability and cytotoxicity was also studied. In vitro transfection efficiency was qualified by florescent microscopy and quantified using flow cytometry technique. Results: cSLN-pDNA complexes were formulated with suitable size and zeta potential. Efficiency/cytotoxicity ratio of cSLN-pDNAs formulations was comparable to linear PEI-25KD-pDNAs polyplexes while exhibiting significantly lower cytotoxicity. Conclusion: Tested formulations were able to deliver immunogenic CP genes efficiently. This data proves the ability of this system as a promising DNA vaccine carrier for leishmaniasis to cover the main drawback of naked pDNA delivery that is rapid elimination from the circulation.